Studies on the Gill Nets of Andhra Pradesh - G., Rajeswari; S.V.S., Ramarao; R., Raghu Prakash (Fishery Technology, 2025)
Artisanal fishing still plays an important role, in spite of domination by trawlers in small-scale fisheries sector. Gill net fishing is one of the popular fishing methods along the east coast of India. However, there are regional variations in their construction and operation. This paper deals with design details of gill nets operated from Srikakulam district to Nellore district of Andhra Pradesh. Polyamide monofilament netting of 0.16 mm to 0.32 mm diameter twine were generally used for construction of gill nets throughout the coast. Polyamide multifilament netting of 210D/1/3 to 210D/6/3 of 20-40 mm mesh size were used for capture of smaller sized fish. Polyamide multifilament netting used in construction of large mesh gill nets targeted at large pelagic fishes, are being replaced by high density polyethylene netting.